The concrete processing of Chinese action metaphors: an ERP study - Zhang, Yuqing; Chen, Shifa; Peng, Yule; Yang, Xin (Frontiers in Psychology, 2024)
The present research adopts ERP (Event-Related Potentials) technology to investigate whether there exists a concreteness effect in the processing of Chinese action verbs within metaphorical context. The mean amplitudes of N400 activated by action metaphors were compared with those activated by literal verbs and abstract verbs. The findings indicated that the Met verbs evoked a significantly larger N400 response at frontal brain region compared to the Abs verbs at a time window 200-500 ms, while the Met verbs elicited a notably greater N400 amplitude specifically at the posterior brain region in comparison to the Lit verbs at 300-500 ms time window. These results may be interpreted as indicating that the comprehension of the Met verbs is based on the concrete action semantics.